CARACTERIZACIÓN EPIDEMIOLÓGICA Y CLÍNICA EN MENORES DE 13 AÑOS QUE VIVEN CON VIH EN COLOMBIA. 2018: UN ESTUDIO DE CORTE TRANSVERSAL - Julieth Carolina Castillo (Asociación Colombiana de Infectología, 2020)
Objective: To describe the epidemiological and clinical characteristics of children living with HIV / AIDS in Colombia. Methods: Retrospective observational study of analytical cross section, carried out in children under 13 years of age living with HIV / AIDS and who were reported to High Cost Diseases Fund in 2018. The prevalence of HIV / AIDS was estimated and children with HIV and children with AIDS were characterized. Results: 655 children had the infection. The HIV / AIDS prevalence was 0.05 (95% CI; 0.04 - 0.07) per 1,000 children. 50.08% were female and 79.85% to the subsidized insurance. Mother-to-child transmission predominated in 89.16%. 83.21% of children used antiretroviral treatment and 50.08% were undetectable. The main diseases that defined AIDS were pneumonia and wasting syndrome. The region of residence, the last CD4 T cells counts and early diagnosis of HIV showed statistical differences between the groups. Conclusion: Reducing mother-to-child transmission of HIV has been a global goal; however, it was the main transmission mechanism in the children under 13 in Colombia. Actions should be directed to prevent transmission and early diagnosis of HIV.